"Butter Crab": an environment‐induced phenotypic variation of Scylla paramamosain with special nutrition and flavour. (3rd December 2018) - Wang, Huan; Tang, Lei; Wei, Hongling; Mu, Changkao; Wang, Chunlin
Abstract: An "abnormal" female Scylla paramamosain, named "Butter crab" (B_♀) is more popular than wild‐type mud crab (CK) with people. Histologically, "butter crab" ovaries are partially degraded, with full of yellow oily substances in body. Composition of the essential nutritional components is quite similar in "butter crab" and CK. In a comparison of fatty acids, B_♀ is richer. A comparison of flavour amino acids and nucleotide in muscle showed that sweet amino acids and bitter amino acids in B_♀ is lower than CK_♀, but umami amino acids are significantly higher in B_♀. However, the umami amino acid content in the gonads is significantly less in B_♀ than CK_♀. Moreover, umami nucleotides in B_♀ muscle is significantly higher. From the perspective of EUC evaluation, the umami taste of CK_ ♀ gonads is strongest, followed by B_ ♀ gonads. In the hepatopancreas, the umami taste ranks CK_♀> B_♀ >CK_♂, and there are no significant differences among muscles in the three groups. In conclusion, the characteristics of "butter crab" are more fragrant and nutritious, with sweet and umami taste. The article systematically scientifically analysed the nutritional composition and flavour characteristics of "butter crab", providing a novel insight for development of S. paramamosain industry.